2019
DOI: 10.12659/ajcr.912282
|View full text |Cite
|
Sign up to set email alerts
|

A Case of T-Cell Large Granular Lymphocytic Leukemia and Renal Immunoglobulin Heavy Chain Amyloidosis

Abstract: Patient: Female, 57Final Diagnosis: Renal heavy chain amyloidosisSymptoms: Fatigue • proteinuriaMedication: —Clinical Procedure: Chemotherapy, consideration of autologous stem cell transplantSpecialty: HematologyObjective:Rare diseaseBackground:T-cell large granular lymphocytic leukemia (T-LGL) is a rare hematological malignancy that currently has no standard therapy. Immunoglobulin heavy chain amyloidosis (AH) involving the kidney is a rare condition and the pathology, diagnosis, clinical characteristics, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Abnormal B-cell activities in LGLL patients could also induce kidney impairment. Zhang M et al reported crescentic glomerulonephritis induced by anti-GBM disease in a patient of T-LGLL ( 9 ). There is also a case report of AH renal amyloidosis type (γ1) with T-LGLL ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal B-cell activities in LGLL patients could also induce kidney impairment. Zhang M et al reported crescentic glomerulonephritis induced by anti-GBM disease in a patient of T-LGLL ( 9 ). There is also a case report of AH renal amyloidosis type (γ1) with T-LGLL ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…This case was published previously before HSCT. 4 Table 1 compares the patients' baseline laboratory characteristics.…”
Section: Casementioning
confidence: 99%
“…In AH, the amyloid fibrils originate from fragments of the Ig heavy chain, whereas in Ig heavy-and-light-chain amyloidosis (AH/AL amyloidosis), both Ig heavy chains and LC contribute to the amyloid fibrils. [2][3][4] AH/AL amyloidosis is the rarest form of Igrelated systemic amyloidosis. 2,3 Renal involvement characterized by proteinuria with or without renal insufficiency is common in AL, AH, and AH/AL amyloidosis.…”
Section: Introductionmentioning
confidence: 99%
“…Cytopenia (autoimmune hemolytic anemia and neutropenia) and rheumatoid arthritis are the most frequent immune disorders associated with LGL, but a wide panel of autoimmune diseases were also observed in patients with LGL, including hematological (red cell aplasia, pernicious anemia, thrombocytopenia), neurological (myasthenia gravis, polyradiculoneuropathy), or rheumatic (Sjögren's syndrome, lupus) disorders [1,2]. To date, only seven cases of renal disease related to LGL have been reported, including renal infiltration by the LGL or heterogeneous glomerulopathies (focal and segmental glomerulosclerosis, vasculitis with anti-glomerular basement membrane antibodies, heavy-chain amyloidosis, glomerulonephritis with endocapillary proliferation) [6][7][8][9][10][11][12]. Recently, we reported two cases of inflammatory renal fibrosis associated with a small-sized T-cell clone (i.e., a clonal population not associated with lymphocytosis and thus requiring dedicated immunophenotyping to be identified) [13].…”
Section: Introductionmentioning
confidence: 99%